Severe and ChRonic Atopic dermatitis Treatment CoHort (SCRATCH): A Danish Real-world Evidence Atopic Dermatitis Treatment Registry - Henrik Hedegaard Pliess Larsen; Ida Vittrup; Iben Frier Ruge; Jesper Elberling; Lone Skov; Kristina Ibler; Gregor Borut Ernst Jemec; Charlotte Gotthard Mørtz; Rasmus Overgaard Bach; Carsten Bindslev-Jensen; Maiken Glud Dalager; Tove Agner; et al. (Medical Journals Sweden, 2022)
Data from real-world use of new systemic treatments in atopic dermatitis (AD) is important for assessing safety and efficacy. The aim of this study is to describe the baseline characteristics of adult patients with moderate-to-severe AD enrolled in the Danish nationwide Severe and ChRonic Atopic dermatitis Treatment CoHort (SCRATCH) database, between October 2017 and August 2021. A total of 282 adult patients were included. Most (62%) were men, the median age at baseline was 43 years (interquartile range (IQR) 29-54 years), and median age at onset of AD was 1 year (IQR 0-6 years). The median Eczema Area and Severity Index at treatment initiation was 19.1 (IQR 11.9-25.7); median Patient Oriented Eczema Measure 21.0 (IQR 16.0-25.0); median Dermatology Life Quality Index 13.0 (IQR 7.0-19.0); and median itch and sleep numerical rating scale scores 8.0 (IQR 6.0-9.0) and 6.0 (IQR 4.0-8.0). Differences were found between the sexes. This registry will provide a source for future efficacy and safety studies.